Comparative effects of guided vs. potent P2Y12 inhibitor therapy in acute coronary syndrome: a network meta-analysis of 61 898 patients from 15 randomized trials - Galli, Mattia; Benenati, Stefano; Franchi, Francesco; Rollini, Fabiana; Capodanno, Davide; Biondi-Zoccai, Giuseppe; Vescovo, Giovanni Maria; Cavallari, Larisa H; Bikdeli, Behnood; Ten Berg, Jurrien; Mehran, Roxana; Gibson, Charles Michael; et al. (European heart journal, 2022)
Guidelines recommend the use of potent P2Y12 inhibitors over clopidogrel for the reduction of ischaemic events in patients with acute coronary syndrome (ACS). However, this comes at the expense of increased bleeding. A guided selection of P2Y12 inhibiting therapy has the potential to overcome this limitation. We aimed at evaluating the comparative safety and efficacy of guided vs. routine selection of potent P2Y12 inhibiting therapy in patients with ACS. We performed a network meta-analysis of randomized controlled trials (RCTs) comparing different oral P2Y12 inhibitors currently recommended for the treatment of patients with ACS (clopidogrel, prasugrel, and ticagrelor). RCTs including a guided approach (i.e. platelet function or genetic testing) vs. standard selection of P2Y12 inhibitors among patients with ACS were also included. Incidence rate ratios (IRR) and associated 95% confidence intervals (CIs) were estimated. P-scores were used to estimate hierarchies of efficacy and safety. The primary efficacy endpoint was major adverse cardiovascular events (MACE) and the primary safety endpoint was all bleeding. A total of 61 898 patients from 15 RCTs were included. Clopidogrel was used as reference treatment. A guided approach was the only strategy associated with reduced MACE (IRR: 0.80, 95% CI: 0.65-0.98) without any significant trade-off in all bleeding (IRR: 1.22, 95% CI: 0.96-1.55). A guided approach and prasugrel were associated with reduced myocardial infarction. A guided approach, prasugrel, and ticagrelor were associated with reduced stent thrombosis. Ticagrelor was also associated with reduced total and cardiovascular mortality. Prasugrel was associated with increased major bleeding. Prasugrel and ticagrelor were associated with increased minor bleeding. The incidence of stroke did not differ between treatments. In patients with an ACS, compared with routine selection of potent P2Y12 inhibiting therapy (prasugrel or ticagrelor), a guided selection of P2Y12 inhibiting therapy is associated with the most favourable balance between safety and efficacy. These findings support a broader adoption of guided approach for the selection of P2Y12 inhibiting therapy in patients with ACS. This study is registered in PROSPERO (CRD42021258603). A guided selection of P2Y12 inhibiting therapy using platelet function or genetic testing improves outcomes among patients undergoing percutaneous coronary intervention. Nevertheless, the comparative safety and efficacy of a guided versus routine selection of potent P2Y12-inhibiting therapy in acute coronary syndrome has not been explored. In a comprehensive network meta-analysis including the totality of available evidence and using clopidogrel as treatment reference, a guided approach was the only strategy associated with reduced major adverse cardiovascular events without any significant trade-off in bleeding. Prasugrel and ticagrelor increased bleeding and only ticagrelor reduced mortality. A guided selection of P2Y12-inhibiting therapy represents the strategy associated with the most favourable balance between safety and efficacy. These findings support a broader adoption of guided P2Y12 inhibiting therapy in patients with acute coronary syndrome.